Economic Sanctions under International Law: Unilateralism, Multilateralism, Legitimacy, and Consequences - Marossi, Ali Z (Springer, 2016)
Since the Second World War, States have increasingly relied upon economic sanctions programs, in lieu of military action, to exert pressure and generally to fill the awkward gap between verbal denunciation and action. Whether or not sanctions are effective remains a point of contention among policymakers. Frequently asked questions include whether any legal order constrains the use of sanctions, and, if so, what the limits on the use of sanctions are. This volume gathers contributions from leading experts in various relevant fields providing a seminal study on the limits of economic sanctions under international law, including accountability mechanisms when sanctioning States go too far. Where there are gaps in the law, the authors provide novel and important contributions as to how existing legal structures can be used to ensure that economic sanctions remain within an accepted legal order.